Pengetahuan dan Dukungan Suami dengan Kejadian Unmet Need Keluarga Berencana pada Pasangan Usia Subur di Wilayah Puskesmas Biromaru Kabupaten Sigi - Sri Yanti Kusika (Jurnal Kesehatan Manarang, 2018)
The impact of unmet need is the unwanted pregnancy will end with unsafe abortion and create morbidity and mortality among mother and child. There are many factors and reasons from reproductive age couple as the cause of high unmet need. This is closely related to knowledge and husband support. This study aims to know the association of knowledge, husband support, and unmet need family planning among reproductive age couple. This study is a cross-sectional study and was conducted on September to October 2017. There are 145 respondents involved in this study using proportional stratified random sampling. Chi-square analysis was used for bivariate statistical analysis. Study result shows that there is a significant association of knowledge (p-value=0.003), husband support (p-value=0,001) and unmet need family planning. It is suggested to health worker for conducting socialization to give information about the importance to be family planning acceptor, involve husband as a support for wife to be family planning acceptor in order to decrease the number of unmet need and indirectly decrease morbidity and mortality among mother and child